A Code-Based Comparison of Seismic Performance of Regular and Plan-Irregular RC Buildings using NBC 105:2020 and IS 1893:2016 (LTU Journal of Advanced Computing & Engineering, 2026)
Nepal's location in an active seismic zone, along with escalating emphasis on architectural aesthetics and land scarcity, has led to increasing plan-irregular buildings that complicate seismic design and compromise structural safety. This study compares the seismic performance of regular and plan-irregular reinforced concrete (RC) buildings designed per IS 1893:2016 and NBC 105:2020 codes, addressing the gap in cross-code, multi-height analyses. For this purpose, one square regular building (RM) and 6 alternative L-shaped irregular buildings (IRM1-IRM6) with 3, 6, 9, and 12 story configurations designed under both codes were analyzed using response spectrum methods in ETABS to evaluate seismic parameters like base shear, drift ratio, displacement, time period, torsion ratio, story stiffness and shear. The findings revealed that NBC-compliant buildings had shorter time periods (up to 40% shorter) but higher base shear (1.75 – 6 times IS), displacement, drift ratio, torsion ratio, story shear, and stiffness than IS-compliant buildings, reflecting stricter seismic demands under NBC that may result in more robust yet cost-intensive designs. Regular models displayed lower base shear (up to 74% reduction) and stiffness, with higher time periods, displacements, and torsional irregularity (TIR > 1.2), indicating increased seismic vulnerability due to asymmetry and stress concentrations. These findings inform resilient seismic design for Nepal’s urban landscape.